Islamic Law Reform in Indonesia: A Perspective on Muhammad Abid Al-Jabiri’s Thought - Putra Halomoan Hsb; Rajali Batubara (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2024)
This study explores the handling of tradition (turath) within Arab society, particularly in the context of modernity and progress. It focuses on the contributions of ‘Abed al-Jabiri, a prominent Muslim philosopher, whose ideas underscore the value of tradition during times of rapid social change. Utilizing a descriptive analysis method, this research examines the interpretation of the Qur’an and Hadith to assess the relevance of ancient scholarly findings to contemporary issues. The study highlights how Islamic feminism, viewed through the lens of Irfani epistemology, seeks to reconstruct these classical insights to align with modern ideals. Islamic feminism is presented as a humanistic ideal rooted in conscience, guided by moral and ethical principles encompassing universal goodness (ma’ruf), individual goodness (khair), happiness (sa’adah), and virtuous deeds (fadhilah). This paper contributes to the discourse on integrating traditional Islamic thought with modern feminist principles, offering a perspective enriched with ethical and spiritual dimensions.